An attempt at evaluation of influence of social stratification upon physical development of girls from Poznań city - Swornowski, Piotr (Anthropological Review, 1984)
The paper deals with influence of socio-economic stratification upon physical development of girls aged 14 to 20 years. Material consists of body measurements of 447 girls living in the city of Poznań. Body height and weight were analysed in the present paper. Only two extreme socio-economic groups were included into the analysis: girls of parents with university education and daughters of physical labourers (primary or vocational education only). It has been found that daughters of university-educated people are on the average taller and lighter than daughters of workingmen. A possible interpretation is that differences in body weight are due to non-economic factors, namely are related to dietary habits and fashions.